Docking Molekuler Senyawa Bioaktif Andrographis paniculata sebagai Kandidat Antimalaria - Rizky Resvita R. Bahi; Moh Rivaldi Mappa; Alia Afrilia Gobel; Tarisya Pobela (Jurnal Farmasi Indonesia, 2023)
Efforts to eradicate malaria have been severely hampered by the growing resistance of Plasmodium falciparum to currently available antimalarial drugs. Therefore, efforts should be made to find and develop new effective antimalarial drugs for the treatment of malaria. One of the plants reported to have antimalarial activity is sambiloto. This study aims to carry out molecular docking of the bioactive compounds contained in sambiloto to obtain potential compounds that have antimalarial activity. In this study, 18 bioactive compounds of sambiloto were docked to 3 target proteins involved in the malaria pathway, namely P. falciparum Plasmepsin II (PDB: 1LEE), PfENR (PDB: 1NHG), and PfDHFR-TS (PDB: 7F3Z) using Autodock 4.0. Based on the docking results, the bioactive compounds with the best activity were analyzed using SwissADME webtool for their pharmacokinetic parameters and drug-likeness. The results showed that the bioactive compound with the best activity against the molecular targets involved in malaria was bisandrographolide C, andrographiside, ninandrographolide, 14-acetylandrographolide, daucosterol, andrographic acid and neoandrographolide. These compounds have the lowest binding energy and interact with important amino acid residues present in the target protein. The bioactive compounds contained in sambiloto have the potential to become candidates for antimalarial drugs and have the opportunity to become oral drugs based on Lipinski’s filter except for andrographiside.